2019
DOI: 10.1126/sciadv.aax5208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phenotyping and image-guided surgical treatment of melanoma using spectrally distinct ultrasmall core-shell silica nanoparticles

Abstract: Accurate detection and quantification of metastases in regional lymph nodes remain a vital prognostic predictor for cancer staging and clinical outcomes. As intratumoral heterogeneity poses a major hurdle to effective treatment planning, more reliable image-guided, cancer-targeted optical multiplexing tools are critically needed in the operative suite. For sentinel lymph node mapping indications, accurately interrogating distinct molecular signatures on cancer cells in vivo with differential levels of sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…were found to be strongly correlated with nodal tumor burden. 46 The results of our pilot study show that the use of cRGDY-PEG-Cy5 A primary end point of the study rested on the need for accurate intraoperative detection of SLNs identified on preoperative 99m Tc lymphoscintigraphy. High concordance (90%) was found between the proportion of ex vivo SLNs identified by technetium Tc 99m sulfur colloid and that optically visualized by cRGDY-PEG-Cy5.5-nanoparticles following early optimization procedures.…”
Section: Discussionmentioning
confidence: 95%
“…were found to be strongly correlated with nodal tumor burden. 46 The results of our pilot study show that the use of cRGDY-PEG-Cy5 A primary end point of the study rested on the need for accurate intraoperative detection of SLNs identified on preoperative 99m Tc lymphoscintigraphy. High concordance (90%) was found between the proportion of ex vivo SLNs identified by technetium Tc 99m sulfur colloid and that optically visualized by cRGDY-PEG-Cy5.5-nanoparticles following early optimization procedures.…”
Section: Discussionmentioning
confidence: 95%
“…Optical SRM with aC' dots will therefore enable the direct study, in particular, of intracellular particle processing details in live cells relevant to questions associated with the clinical translation of diagnostic as well as therapeutic C' dot applications. [27,[62][63][64][65]…”
Section: Doi: 101002/adma202006829mentioning
confidence: 99%
“…[36][37][38], as a drug delivery vehicle offering improved therapeutic properties over the corresponding native drug in a patientderived model of NSCLC. Our prior work has shown that dyeencapsulated C 0 dots can be surface modified with an array of functional groups (37)(38)(39)(40)(41)(42)(43) and radiotracers (40,44) for mapping disease in both surgical (45) and nonsurgical settings (39,41), as well as for investigating biological properties and targeted inhibition in a high-grade glioma model (46). In addition, we have demonstrated the successful conjugation and in vitro therapeutic activity of a protease-sensitive gefitiniblinker construct to an earlier generation silica nanoparticle, which was found to inhibit EGFR signaling in vitro (47).…”
Section: Introductionmentioning
confidence: 99%